Enhancing Student Engagement in Science Practicum in Distance Higher Education for Quality Education (SDG 4) - Widiasih, Widiasih; Zakirman; Sukmaning Adji, Sandra; Firmansyah, Juli; Ekawati, Ratna; Sumardani, Dadan; Chaw, Ei Phyu (Jurnal Pendidikan IPA Indonesia, 2025)
This study identifies and analyzes the key factors influencing students’ engagement in science practicum activities within the Open and Distance Higher Education (ODHE) context. 127 students from diverse regions of Indonesia participated in this quantitative study, which assessed perceptions regarding academic challenges, learning interaction, collaborative learning, and the use of technology in online laboratory settings. The results indicate that tutorial modality, employment status, academic achievement (GPA), and residential area significantly influence engagement levels. Students participating in web-based classes and receiving consistent learning feedback reported higher engagement. Conversely, laboratory report writing emerged as a primary challenge, highlighting the urgent need for enhanced scientific writing literacy. The findings are discussed within the Community of Inquiry (CoI) and Self-Determination Theory (SDT) frameworks, emphasizing the importance of teaching presence, social collaboration, and learner autonomy in digital learning environments. Notably, students from rural areas exhibited high motivation despite infrastructural limitations. The study recommends redesigning learning models to include targeted support, structured digital practicum modules, and formative feedback mechanisms. This research contributes to developing inclusive, adaptive, and effective science education practices in ODHE while supporting achieving Sustainable Development Goal (SDG) 4: Quality Education.